LOCUS OF CONTROL DAN PENGALAMAN KERJA TERHADAP INDEPENDENSI - Warsoko, K. Soetanto (Journal of Management and Business, 2007)
Independency is important ethical behavior of public accountant. Auditors’ behavior is observed to determine independency because auditor is profession which needs public trust. In order to make ethical behavior or to change unethical behavior, the first thing should know is the factors that affect behavior and how strong their effect. Previous researches showed that individual factors have been found to have significant impacts on ethical behavior, especially independency. The objective of this study was to determine whether the individual difference factors of locus of control and job experience affect the independency. The research method used in this study was survey with questionnaire. Data collected with snowballing method and directly to respondents. T-test was used to test the hypothesis. The result showed that auditors with internal locus of control were found to behave more independent than those with external locus of control. There were no significant differences between auditors with difference job experience.